Assessment of pumped hydropower energy storage potential along rivers and shorelines. (September 2022) - Görtz, J.; Aouad, M.; Wieprecht, S.; Terheiden, K.
Abstract: The increasing share of renewable energy sources, e.g. solar and wind, in global electricity generation defines the need for effective and flexible energy storage solutions. Pumped hydropower energy storage (PHES) plants with their technically-mature plant design and wide economic potential can meet these demands. Especially, in the vicinity of volatile renewable energy plants they can directly balance frequency fluctuations with short reaction times and large capacities. Therefore, site identification for new pumped hydropower energy storage schemes is a crucial issue intensifying the research needs of developing new algorithms for automated search routines. As current methods neglect shape constraints for ring dams, a new method that incorporates the evaluation of the shape is proposed. In addition, the area slope threshold is transformed into site quality measures removing a hard cut-off at a certain limit. The developed method is able to locate and evaluate suitable ring dam locations along rivers but can also be applied to shore lines or existing lower reservoirs. The effectiveness of the routine is demonstrated and successfully verified by locating promising locations along two rivers in Chile. Highlights: Review of current methods and criteria for PHES site identification. Automated algorithm to identify sites for PHES along rivers and shorelines. Assessment of sites according to topological characteristics and the area shape. Topological quality control by using variable threshold values. Verification of the proposed model for two Chilean rivers.